2006
DOI: 10.1097/01202412-200607000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver and intraobserver reliability of radiographic evidence of bone healing at osteotomy sites

Abstract: Plain radiographs are commonly used to evaluate the degree of bone healing after an osteotomy and the application of an external fixator. The purpose of the study was to assess intraobserver and interobserver reliability in determining bone healing, defined as bridging callus across three of four cortices, of osteotomy sites on radiographs. Substantial intraobserver reliability and a high intraobserver percentage agreement were found. Interobserver reliability was moderate and interobserver percentage agreemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 5 publications
0
23
0
1
Order By: Relevance
“…The radiographic analysis showed that most of the third molar, 41.26% (26) were mesioangualr impactions, followed by vertical 22.22% (14), horizontal 20.63% (13), and distoangular 15.87% (10) [Table/ Fig-6,7]. +500 Celsius and this high temperature leaves only pure inorganic structure and thus removes the risk of transmission of any disease [6].…”
Section: Resultsmentioning
confidence: 99%
“…The radiographic analysis showed that most of the third molar, 41.26% (26) were mesioangualr impactions, followed by vertical 22.22% (14), horizontal 20.63% (13), and distoangular 15.87% (10) [Table/ Fig-6,7]. +500 Celsius and this high temperature leaves only pure inorganic structure and thus removes the risk of transmission of any disease [6].…”
Section: Resultsmentioning
confidence: 99%
“…The distraction rate (in millimeters per day) was defined as the length of callus regeneration observed on the radiograph in millimeters divided by the time from the start to the end of distraction in days. A previous study [1] showed high intraobserver and interobserver reliability in determining bony union (defined as bridging callus across three of four cortices) of the osteotomy site on radiographs. The healing index was defined as the total treatment period with the fixator in situ, divided by the length of bone growth in centimeters.…”
Section: Methodsmentioning
confidence: 99%
“…However, Anand et al [16] found inter-observer percentage agreement to be less than half between all involved orthopedic surgeons, supporting the observation that assessment of bone healing by radiography after distraction osteogenesis is subjective. Starr et al [16] investigated the reliability of using radiographs as a method to assess bone healing and determined that the variation in the assessment of the number of cortices was slightly better than chance.…”
Section: Standard Radiographymentioning
confidence: 99%
“…Starr et al [16] investigated the reliability of using radiographs as a method to assess bone healing and determined that the variation in the assessment of the number of cortices was slightly better than chance. The authors concluded that low refracture rates after removal of an external fixator may be more an indicator of clinical judgment by experienced practitioners than the accuracy of using radiographic evaluation.…”
Section: Standard Radiographymentioning
confidence: 99%
See 1 more Smart Citation